Desempeño de directivos en redes educativas rurales en el nivel inicial - Sosa-Gutierrez, Fredy (2023)
The research determines the performance of directors of the initial level in rural educational networks in the Local Educational Management Unit El Collao - Ilave. The work is framed in a non-experimental methodology, analyzing the instrument, Work Performance Evaluation Sheet of the Director, designed and approved by the Ministry of Education of Peru. The population is made up of the directors of the rural area of ??the district of Pilcuyo. Being its results; Of the six competencies and 20 managerial performance criteria, only in 10 indicators they achieve the value of always, in 8 criteria they rarely obtain and in indicators 3,5,7 and 15 they showed to be located on the scale never. Concluding that; the actions or performances of the directors in 50% are favorable, in 40% it is regular and in 10% it is unfavorable. This calls for reflection and seeking ways to substantially improve the conduct of educational establishments.